Iona: some results from recent work - Haggarty, Alison M; Shiel, Robert; Lane, Alan; Campbell, Ewan; Askew, G P (Proceedings of the Society of Antiquaries of Scotland, 1989)
A service trench east of the Abbey confirmed the presence of the plaggen soil encountered previously (a high-quality soil deliberately introduced to the site). Important group of early medieval pottery with stratified contexts and a 14C date. A R (Pottery is discussed in relation to Souterrain ware - Ed)